Chemistry of biomolecules - Bhutani, S. P. (CRC Press, Taylor & Francis Group, 2020)
"Biomolecules are molecules that are involved in the maintenance and metabolic processes of all living organisms. This fully revised second edition offers extensive coverage of important biomolecules from an organic chemistry point of view. The author discusses carbohydrates, amino acids, peptides, proteins, enzymes, pyrimidines, purines, nucleic acids, terpenoids, and lipids. The various topics are described in simple, lucid language and explain the mechanisms of the reactions wherever required. Ideal for upper level undergraduates, graduates and researchers"--